Peran Dukungan Sosial dan Kecemasan Karier Terhadap Kesiapan Kerja Final Year Students Generasi Z - Kayla Aliyah Diva Hiaruman; Muhammad Fikri Pratama; Ernawati Ernawati (Humanitas (Jurnal Psikologi), 2025)
Final-year Generation Z students face challenges in preparing themselves to enter the workforce, including academic pressure and career anxiety. Work readiness is shaped by the influence of internal and external factors such as social support and career anxiety; however, previous research has not yet explained the dynamics between these three aspects. This study was conducted to examine the role of social support and career anxiety on the work readiness of final-year Generation Z students. The study involved 430 students (aged 19–25 years) selected through convenience sampling. Data were collected using the Work Readiness Scale, Career Anxiety Scale, and Multidimensional Scale of Perceived Social Support, and analyzed with multiple linear regression. The results revealed that social support had a significant positive effect, while career anxiety had a stronger negative effect. Career anxiety emerged as the main barrier, whereas social support acted as a driver of work readiness. Psychosocial interventions and career counseling are recommended to improve students’ work readiness.